Beyond Income and Balance Sheet: Measuring Quedancor Region X - Bokingo, Kizzy Ann R. (JPAIR Multidisciplinary Research, 2009)
The study focused on customer relationship management (CRM) of the Self Reliant Team (SRT) financing Model of QUEDANCOR. The scope includes the SRT clients from 12 selected Municipalities. The objectives include determining the profile of SRT Model clienteles, describing the credit experience as clients of QUEDANCOR and SRT Cooperatives, comparing feedbacks for QUEDANCOR against SRT Cooperatives and against profiles of the clients, and assessing changes of client welfare with SRT financing. The results shows varied feedbacks from respondents on the seven indicators: convenience and comfort, understanding the fundamental principles of SRT, speed and timeliness, loan packaging, treatment from creditors, communication process and improving services as provided by the SRT Players, QUEDANCOR and the SRT Cooperatives. Majority of the respondents claimed the model made them better off economically. However, concerns were also identified as areas for improvement by the financing model